2015
DOI: 10.1038/ncomms8164
|View full text |Cite
|
Sign up to set email alerts
|

Directional cell movement through tissues is controlled by exosome secretion

Abstract: Directional cell movement through tissues is critical for multiple biological processes and requires maintenance of polarity in the face of complex environmental cues. Here we use intravital imaging to demonstrate that secretion of exosomes from late endosomes is required for directionally persistent and efficient in vivo movement of cancer cells. Inhibiting exosome secretion or biogenesis leads to defective tumour cell migration associated with increased formation of unstable protrusions and excessive directi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

37
536
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 507 publications
(574 citation statements)
references
References 49 publications
37
536
1
Order By: Relevance
“…We then further purified UC-Exo by sedimentation into a density gradient of Optiprep (DG-Exo) as described previously. 6 Consistent with our previous publication, 6 Western blot analysis revealed that FN is carried by HT1080 UCExo as well as DG-Exo but not on MV ( Fig. 2A).…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…We then further purified UC-Exo by sedimentation into a density gradient of Optiprep (DG-Exo) as described previously. 6 Consistent with our previous publication, 6 Western blot analysis revealed that FN is carried by HT1080 UCExo as well as DG-Exo but not on MV ( Fig. 2A).…”
Section: Resultssupporting
confidence: 91%
“…6 We further found that fibronectin carried by exosomes promotes cell adhesion, explaining the speed defect of exosome secretion-inhibited cells. 6 To explore the role of EVs and their cargoes in cancer cell chemotaxis, we performed a similar approach. Exosomes were isolated from the conditioned media of HT1080 fibrosarcoma cells by serial centrifugation (ultracentrifuged exosomes, UC-Exo).…”
Section: Resultsmentioning
confidence: 65%
See 3 more Smart Citations